Pursuing Truth How Gender Shaped Catholic Education at the College of Notre Dame of Maryland - Oates, Mary J. (Cushwa Center Studies of Catholicism in Twentieth-Century America, 2021)
In Pursuing Truth, Mary J. Oates explores the roles that religious women played in teaching generations of college and university students amid slow societal change that brought the grudging acceptance of Catholics in public life. Across the twentieth century, Catholic women's colleges modeled themselves on, and sometimes positioned themselves against, elite secular colleges. Oates describes these critical pedagogical practices by focusing on Notre Dame of Maryland University, formerly known as the College of Notre Dame of Maryland, the first Catholic college in the United States to award female students four-year degrees. The sisters and laywomen on the faculty and in the administration at Notre Dame of Maryland persevered in their work while facing challenges from the establishment of the Catholic Church, mainline Protestant churches, and secular institutions. Pursuing Truth presents the stories of the institution's female founders, administrators, and professors whose labors led it through phases of diversification. The pattern of institutional development regarding the place of religious identity, gender and sexuality, and race that Oates finds at Notre Dame of Maryland is a paradigmatic story of change in US higher education. Similarly representative is her account of the school's effort, from the late 1960s to the present, to maintain its identity as a women's liberal arts college. Thanks to generous funding from the Cushwa Center at the University of Notre Dame, the ebook editions of this book are available as Open Access (OA) volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other Open Access repositories.